Corporate makeover for narcissism: The role of the CEO in asset revaluation and acquisition performance - Wati, Erna; Itan, Iskandar; Derista, Fanny; Karjantoro, Handoko (Journal of Accounting and Investment, 2025)
Research aims: This study aims to analyze the impact of CEO narcissism on the correlation between asset revaluation and acquisition performance, focusing on how narcissistic traits improve the efficiency of asset revaluation in corporate decision-making.Design/Methodology/Approach: The study employs Partial Least Squares methodology within Structural Equation Modeling to analyze secondary data from Indonesian companies listed on the Indonesia Stock Exchange between 2017 and 2021. The sample is limited to companies engaged in merger and acquisition activities during the observation period. Following the selection criteria, the final sample consists of 51 eligible firms.Research findings: The findings indicate that revaluing assets improves companies’ financial position and market perception. Additionally, the impact is heightened by CEO narcissism, as narcissistic CEOs use their confidence and propensity for risk-taking to capitalize on asset revaluation for aggressive acquisition tactics. It leads to improved company performance, especially in mergers and acquisitions.Theoretical contribution/ Originality: This study contributes theoretically by extending the application of signalling theory and the resource-based view. It positions CEO narcissism as a strategic signal influencing acquisition performance through asset revaluation. The study adds to existing research on corporate leadership and financial strategy, providing valuable perspectives for scholars and professionals in management and corporate finance.Practitioner/Policy implication: The study indicates that corporations gain advantages by choosing CEOs with narcissistic characteristics, as they are more inclined to employ asset revaluation to pursue ambitious acquisition opportunities strategically. The results suggest that firms may benefit from leadership that strategically leverages narcissistic traits to enhance corporate restructuring outcomes.Research Limitations/Implications: The limitation of this study is its focus on Indonesian companies, which potentially restricts the generalizability of the results to different regions or markets.